Photo Documentary on Motorcycle Crash Victims: A Preliminary Study on Road Users' Response - Y. Ghani; Z. Mohd Jawi; K.A. Abu Kassim; M.H. Zakaria; M.D. Radzuan; A.T. Azizan (Journal of the Society of Automotive Engineers Malaysia, 2022)
The gravity of motorcycle crash fatalities in Malaysia requires an out-of-the-box and creative approach to alleviate the situation. While currently, various interventions emphasize science through education, engineering, and enforcement, a subtle approach with art in promoting road safety messages would be worth discovering. Therefore, this preliminary research explores the effectiveness of post-crash images of motorcycle victims in communicating road safety awareness. The series of photographs in this documentary is suitable for various road safety campaign platforms. A total of 20 motorcycle crash victims were documented using 35mm black and white film photography. The victims (or their respective caretakers) were interviewed to record the events that led to the crash and the post-crash implications on social and economic. The photos were traditionally printed (in the darkroom) on 16x20 inch Ilford Multigrade FB Classic Paper. The series were then exhibited at the Vehicle Safety Week in Melaka and Sekolah Kebangsaan Jalan Bukit 1, Kajang. To investigate the effectiveness of the message from the photographs, the audience was requested to answer a questionnaire in Google Form via the WhatsApp application. From 45 survey respondents, the results showed that most of them agreed that black and white film photography is effective in promoting safer roads; and such exhibitions should be held frequently. In conclusion, the use of black and white photography of crash victims' sufferings can stir up the audience's emotion and raise awareness of motorcycle safety. Furthermore, the use of these photographs should be amplified into other media platforms, especially social media to reach more audiences.